The temporal regimes of HIV/AIDS activism in Europe: chrono-citizenship, biomedicine and its others - Dziuban, Agata; Sekuler, Todd (Critical public health, 2021)
HIV/AIDS is known to have fundamentally transformed fields of biomedical research, the governance of health, and state-citizen relations. Based on research that was developed to analyze these transformations within HIV/AIDS activism at the European-level, we offer the term chrono-citizenship to describe the influence of time in constructs of citizenship. We argue that the temporal regime of biomedicine, or modes of governance that depend on biomedical understandings of time, have come to dominate HIV/AIDS narratives, policies and programs. Building on oral histories and three years of fieldwork in spaces of European-level networks and health-governing bodies, we suggest that citizenship in the field of HIV/AIDS has been defined through multiple, intersecting and, at times, antagonistic temporal regimes. To illustrate this, we expose the regime of loss, through which mourning, often denied space in the present, bears potential for new forms of subjectivity and community; the regime of sustainability, which centers the planning and surveillance of budgets over service provision in a climate unfriendly to human rights; and the regime of chronic crisis, in which persistence becomes a form of political agency against ongoing exclusion and disappointment. As we show, unearthing varied temporalities helps to denaturalize biomedical understandings of time, and invites a rethinking of the foundations needed to reach the 'end of AIDS' sought by civil society, UNAIDS and other health-governing bodies.